Proximate Analysis of Melon Seeds Available in Bangladesh (Dhaka University Journal of Science, 2022)
The seeds of winter (wax gourd), long (bottle gourd) and large (pumpkin) melon were analyzed for nutritional parameters mainlyprotein, fat/oil, carbohydrate, dietary fiber, protein, minerals and moisture and fatty acids composition. The double beam ultravioletvisible spectrophotometer was used for analysis of total sugar. The protein content was determined using the Kjeldahl method. An atomic absorption spectrophotometer was used to quantify minerals (Fe, Cu, and Zn). Fatty acid was analyzed by gas chromatography(GC) equipped with a flame ionization detector (FID). From the proximate analysis, it was found that the winter melon (wax gourd)seeds contain protein, oil, carbohydrate, soluble dietary fiber, moisture and ash content of 19.71, 16.46, 56.48, 3.10, 68.88 and 4.26%, respectively. Similarly, long melon (bottle gourd) was found to contain 16.12, 13.61, 46.88, 2.2, 76.45 and 5.2% of protein, oil,carbohydrate, soluble dietary fiber, moisture and ash, respectively. The contents of protein, oil, carbohydrate, soluble dietary fiber,moisture and ash in large melon (pumpkin) seeds were found to be 29.64, 18.17, 55.32, 1.3, 79.53 and 5.12%, respectively. In mineralanalysis, iron, copper, and zinc contents were found to be 6.75, 0.62, and 6.10 mg/100g in winter melon; 7.8, 1.63, and 4.25 mg/100gin long melon; and 13.95, 1.15, and 5.11 mg/100g in large melon, respectively.Dhaka Univ. J. Sci. 70(1): 58-63, 2022 (January)